Uncanny Carnivalesque Effects in Curacao: The Longest Month by Diana Lebacs - Ineke Phaf (Universidad de Quintana Roo, 2001)
This work calls for a re-dimension of literary creation regarding female writers from Cura ao Ñ mainly catalogued as literature for young people Ñ through an analysis of two publications: firstly, Mundu yama sinta mira. Womanhood in Cura ao (Ansano et al.), which gathers poems, short stories as well as essays written in Papiamentu, English, Dutch and Spanish and deals with the role of women within cultural life. The other book, The longest month (De langste maand), written by Diana Lebacs, is a novel written in Dutch and should be considered as a valuable document for future research with regards to modernity in the Caribbean.